2021
DOI: 10.3389/fphar.2021.690141
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Assessment of Bromochlorophene: Single and Repeated-Dose 28-Day Oral Toxicity, Genotoxicity, and Dermal Application in Sprague–Dawley Rats

Abstract: Bromochlorophene (BCP) has shown good properties in sterilization and antibacterial activity and is widely used as a household chemical. We evaluated the genotoxicity, single and repeated-dose 28-day oral toxicity, and dermal application of a BCP suspension in Sprague–Dawley (SD) rats. For the single-dose toxicity study, a dose of 25–1,000 mg per kg of bodyweight (mg/kg b.w.) of BCP was given once orally to SD rats. Mortality and clinical signs were observed and recorded for the first 30 min after treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the in vivo dermal study, 2.34 mg/kg of BCP was applied to rat dorsal skin and 12.2 ± 2.63% of bioavailability was observed. However, in another in vivo dermal study [9], BCP absorption in the hydrogel formulation was 29.25 ± 6.09% following 0.262 mg/kg rat dorsal application. In accordance with Im et al, the application doses affected skin absorption.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the in vivo dermal study, 2.34 mg/kg of BCP was applied to rat dorsal skin and 12.2 ± 2.63% of bioavailability was observed. However, in another in vivo dermal study [9], BCP absorption in the hydrogel formulation was 29.25 ± 6.09% following 0.262 mg/kg rat dorsal application. In accordance with Im et al, the application doses affected skin absorption.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the results of in silico and in vitro studies have shown that BCP interferes with nuclear receptor function and acts as an antagonist of the androgen receptor, estrogen receptor α, glucocorticoid receptor, and thyroid receptors α and β [8]. In addition, in a study by Won et al on repeated-dose oral toxicity of BCP for 28 days, the relative weight of the kidneys in female rats increased at a dosage of 500 and 1000 mg/kg, and their hematological and histopathological characteristics were altered at these dosages [9]. They also reported in vivo dermal absorption in rats, but the analysis method used for the evaluation of BCP concentration and the formulation applied to the skin were unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring urine output, proteins, and glucose levels can help determine renal toxicity (Patel et al, 2018). In humans and animals, exposure to various hazardous chemicals raises oxidant levels and induces oxidative DNA damage, which leads to cellular damage and tissue necrosis (Won et al, 2021). All organs showed normal histology and indicated no pathological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Only the micronucleus test result was unable to obtain accurate genotoxicity (mutagenicity) information; therefore, further genotoxicity test is required for confirmation of genotoxicity of CEAE. In addition to the micronucleus test, other in vitro assay systems have been also used to evaluate the genotoxic potential of tested substances including the Ames test, chromosomal aberration test, and Comet assay [ 27 – 29 ]. In this study, the in vitro chromosomal aberration test in CHL cells indicated that CEAE did not produce chromosomal damage-inducing potential ( Table 4 ), further underpinning the ascertainment of nongenotoxicity of CEAE.…”
Section: Discussionmentioning
confidence: 99%